Understanding Pedagogical Competence in the Context of Islamic Religious Education - Ely Ernawati (Yayasan Bayt Shufiya Nusantara, 2024)
This research aims to examine in depth the importance of pedagogic competence for Islamic Religious Education teachers as one of the fundamental elements in supporting the quality of learning. This study uses the Systematic Literature Review (SLR) method by searching various relevant scientific articles that have been published through Google Scholar. Data analysis was carried out by selecting literature based on certain inclusion and exclusion criteria, then synthesizing it to produce a complete understanding of the research theme. The results of the study show that the pedagogic competence of Islamic Religious Education teachers must continue to be improved to answer the increasingly complex educational challenges, especially in the midst of the rapid development of science and technology. This improvement is crucial so that teachers are able to integrate Islamic values into contextual, adaptive, and transformative learning.